2020
DOI: 10.1002/onco.13600
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Exceptional Responders to Cancer Therapy

Abstract: Background. The vast majority of metastatic cancers cannot be cured. Palliative treatment may relieve disease symptoms by stopping or slowing cancer growth and may prolong patients' lives, but almost all patients will inevitably develop disease progression after initial response. However, for reasons that are not fully understood, a very few patients will have extraordinary durable responses to standard anticancer treatments. Materials and Methods. We analyzed exceptional responders treated at Fox Chase Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Accordingly, perhaps rather than pursuing different patterns of care for individuals with EO-CRC, clinicians rather should continue to evaluate the opportunity of novel clinical and translational studies aimed at identifying who may benefit most from a specific type of treatment while sparing toxicities. 4,5,12,46,47 Meanwhile, prospective studies incorporating patient-reported outcomes, such as quality of life, symptom burden, and shared decision making, should be among the next steps to define the impact of more intensive clinical management of patients with EO-CRC.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, perhaps rather than pursuing different patterns of care for individuals with EO-CRC, clinicians rather should continue to evaluate the opportunity of novel clinical and translational studies aimed at identifying who may benefit most from a specific type of treatment while sparing toxicities. 4,5,12,46,47 Meanwhile, prospective studies incorporating patient-reported outcomes, such as quality of life, symptom burden, and shared decision making, should be among the next steps to define the impact of more intensive clinical management of patients with EO-CRC.…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing studies using large oncogene panels in advanced cancers find an actionable DNA mutation in 5–35% of cases, depending on associated tumor histology 3 , 4 . Although there are exceptional responders to targeted therapy 5 , 6 , rarely do advanced cancer patients with a candidate “targetable” mutation exhibit long-term survival. Thus, there is a movement in precision oncology to implement functional cell-based assays to complement genomic panels 7 .…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial overexpression of the cholecystokinin type 2 receptor (CCK2R) in tumor cells of the gastrointestinal tract compared with normal cells at the time of tumor emergence. Besides, overexpression is particularly prominent in some regions of colon cancer, colorectal cancer, and gastric cancer cell lines [ 12 14 ]. The cholecystokinin (CCK) secreted by intestinal mucosal cells is highly compatible with the cholecystokinin-B receptor (CCKBR), which will accumulate in large quantities around the cancerous tissues and promote the infiltration and migration of tumor cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%